Job involvement and its indicative applications to prevent occupational stress - DHOU, Fouzia; MECHERI, Soulef (Social Empowerment Journal, 2021)
Academic research on the notion of job involvement is still relatively recent, but there are indications that confirm its importance and its positive effects on the psyche of the worker and his feeling of comfort in his work instead of feeling psychological or professional stress, because it is the feeling of happiness and psychological comfort of the worker in the accomplishment of his tasks to the point of being ready to make extra efforts for free in a way of accomplishing the tasks assigned to him. Consequently; This study aims to draw attention to the concept of job involvement, its importance and its applications in the field of professional counseling by activating its strategies for the prevention of professional psychological stress, then arriving to submit proposals and recommendations that would clarify the mechanisms ensure professional psychological stress by investing job involvement strategies as one of the most important and modern concepts provided by positive psychology.